Following Healthy Pregnancy by NMR Metabolomics of Plasma and Correlation to Urine - Pinto, Joana
This work presents the first NMR metabolomics study of maternal plasma during pregnancy, including correlation between plasma and urine metabolites. The expected decrease in circulating amino acids early in pregnancy was confirmed with six amino acids being identified as required by the fetus in larger extents. Newly observed changes in citrate, lactate, and dimethyl sulfone suggested early adjustments in energy and gut microflora metabolisms. Alterations in creatine levels were also noted, in addition to creatinine variations reflecting alterations in glomerular filtration rate. Regarding plasma macromolecules, HDL and LDL+VLDL levels were confirmed to increase throughout pregnancy, although at different rates and accompanied by increases in fatty acid chain length and degree of unsaturation. Correlation studies suggested (a) an inverse relationship between lipoproteins (HDL and LDL+VLDL) and albumin, with a possible direct correlation to excreted (unassigned) pregnancy markers resonating at d 0.55 and d 0.63, (b) a direct link between LDL+VLDL and N-acetyl-glycoproteins, together with excreted marker at d 0.55, and (c) correlation of plasma albumin with particular circulating and excreted metabolites. These results have unveiled specific lipoprotein/protein metabolic aspects of pregnancy with impact on the excreted metabolome and, therefore, provide an interesting lead for the further understanding of pregnancy metabolism.